Factors predicting barriers to exercise in midlife Australian women. (May 2016) - McGuire, Amanda; Seib, Charrlotte; Anderson, Debra
Highlights: Chronic diseases are largely preventable and are largely attributable to modifiable lifestyle risk factors, including lack of exercise. This study investigated the perceived barriers to exercise in 225 midlife Australian women with an average age of 50.9 who completed an online surve. Hierarchical regression modelling found that the predictors of perceptions of exercise barriers are exercise benefits perceptions, exercise self-efficacy, and physical and mental well-being. These findings have application to the design and delivery of exercise behavior change interventions for midlife women. Abstract: Objectives: Chronic diseases are the leading cause of death and disability worldwide. They are, though, largely attributable to modifiable lifestyle risk factors, including lack of exercise. This study aims to investigate what factors predict perceptions of barriers to exercise in midlife women. Study design: This cross-sectional descriptive study collected data from midlife Australian women by online questionnaire. Volunteers aged between 40 and 65 years were recruited following media publicity about the study. Main outcome measures: The primary outcome measure was perceived exercise barriers (EBBS Barriers sub-scale). Other self-report data included: exercise, smoking, alcohol, fruit and vegetable consumption, body mass index, physical and mental health and well-being (MOS SF-12v2) and exercise self-efficacy. Results: On average, the 225 participants were aged 50.9 years (SD = 5.9). The significant predictors of perceived barriers to exercise were perceived benefits of exercise, exercise self-efficacy, physical well-being and mental well-being. These variables explained 41% of the variance in the final model ( F (8219) = 20.1, p < .01) Conclusions: In midlife women, perceptions of barriers to exercise correlate with beliefs about the health benefits of exercise, exercise self-efficacy, physical and mental well-being. These findings have application to health promotion interventions targeting exercise behaviour change in midlife women.